Universal basic income. Theory and practice - Misztal, Piotr (Managerial Economics, 2019)
A universal basic income is fi nancial income agreed to all members of society without the need to provide work. The right to this income and its level are universal and independent of the size and structure of the household. In addition, a universal income is paid regardless of the income of the citizens from other sources. The purpose of the article is to provide a theoretical and empirical analysis of a universal basic income, with a particular emphasis on the origin and re-sults of introducing this instrument. In the text, research methods are used based on literature studies in macroeconomics and economic policies as well as statistical and descriptive methods based on the data published by international economic institutions (Organization for Economic Co-operation and Development and the World Bank).